MENILIK MASYARAKAT MINANGKABAU MELALUI RUMAH GADANG - Muhdaliha M.Sn, Benny (Kartala, 2022)
Cultural artifacts and artefactual are a representation of a number of values (intrinsic and extrinsic) from the society in which they are produced. The traditional house of the Minangkabau tribe, Rumah Gadang, has a basic function as a place to live but on the other hand it is also a symbol of the existence of a tribe in Minangkabau. Therefore, Rumah Gadang has a very complex relationship between its function and social meaning. The architectural style and the allocation of space are not only for pursuing beauty but also represents the psychological and socio-political life of the people. This study aims to explore the relationship between Rumah Gadang and the human interaction in it by using a qualitative descriptive method through a visual perception approach. Rumah Gadang as an important visual symbol for the Minangkabau community, which also implies the cultural values of its people through the purpose of making and allotment of each room in it.